Translation to Polish, cross-cultural adaptation, and validation of the Bristol Stool Form Scale among healthcare professionals and patients - Wojtyniak, Katarzyna; Szajewska, Hania; Dziechciarz, Piotr (Gastroenterology Review/Przegląd Gastroenterologiczny, 2018)
Introduction : The seven-point Bristol Stool Form Scale (BSFS), which refers to seven pictures of different forms of stool, is a commonly used instrument to assess stool consistency. Aim : To translate, cross-culturally adapt, and validate the BSFS for its use in Poland. Material and methods : The steps included forward translation, reconciliation, backward translation, comparison of the two English versions and validation of the translation, pilot testing, proofreading, approval of the final version of the target language BSFS, and validation. The latter process involved healthcare professionals (physicians and nurses), healthy adults, and adult patients with gastrointestinal disorders, who were asked to correlate images of seven types of stools with their descriptions. All available subjects were asked to repeat the survey to assess test-retest reliability. The primary outcome measures were validity (accuracy) and reliability (repeatability). Results : A total of 320 subjects took part in the validation study (80/group). Overall, concordance between descriptions and pictures was 78.7%, and the overall  index was good (0.75, 95% confidence interval (CI): 0.73 to 0.77). Test-retest assessment was performed in 170 (53.1%) subjects within a mean interval of 5.9 ±2.5 days. Overall, concordance between definitions and pictures for the re-testing phase was 90.7% with a  index of 0.89 (95% CI: 0.87 to 0.91). Conclusions : As a result of the translation and cultural adaptation process, a final Polish version of the BSFS was created. The substantial validity and reliability of this Polish version was demonstrated.